Enhanced efficiency of photovoltaic panels by integrating a spray cooling system with shallow geothermal energy heat exchanger. (April 2019) - Yang, Li-Hao; Liang, Jyun-De; Hsu, Chien-Yeh; Yang, Tai-Her; Chen, Sih-Li
Abstract: In this study, a cooling system with shallow-geothermal energy is experimentally investigated to mitigate the photovoltaic panel conversion efficiency decline problem, and a mathematical model is built for predicting the system performance. This cooling system cools the panel by spraying water onto the reverse of the panel, and returns the water to the tank. To enhance the cooling capacity, the recycled water is collected in a U-shaped borehole heat exchanger (UBHE), which is installed in an existing well, and the water exchanges heat with shallow-geothermal energy. Finally, the panel is again sprayed with water to cool it. The experiments are comprised of three stages: The first involved the panel operating without cooling system. The second involved the panel operating with a cooling system but without a UBHE. The third is the cooling system operating with a UBHE. The experimental results and the mathematical models show the same trend: The cooling system can improve the panel conversion efficiency; moreover, as the temperatures and the number of panels increase, the benefit becomes obvious. For a plant factory powered by panels, for example, this cooling system can improve the efficiency by 14.3%, and its equipment costs recovered in 8.7 years with this system. Graphical abstract: Highlights: A cooling system, combined with shallow geothermal energy, is applied to a photovoltaic panel system for the mitigation of the efficiency decline caused by high temperatures. The U-shaped borehole heat exchanger can maintain the cooling capacity of the cooling system while reducing energy consumption. A mathematical model is developed for estimating a photovoltaic panel's temperature and conversion efficiency under different conditions.